Co-chaperones of Hsp90 in Plasmodium falciparum and their concerted roles in cellular regulation. Issue 9 (21st February 2014) - CHUA, CHUN-SONG; LOW, HUIYU; SIM, TIOW-SUAN
SUMMARY: Co-chaperones are well-known regulators of heat shock protein 90 (Hsp90). Hsp90 is a molecular chaperone that is essential in the eukaryotes for the folding and activation of numerous proteins involved in important cellular processes such as signal transduction, growth and developmental regulation. Co-chaperones assist Hsp90 in the protein folding process by modulating conformational changes to promote client protein interaction and functional maturation. With the recognition of Plasmodium falciparum Hsp90 (PfHsp90) as a potential antimalarial drug target, there is obvious interest in the study of its co-chaperones in their partnership in regulating cellular processes in malaria parasite. Previous studies on PfHsp90 have identified more than 10 co-chaperones in P. falciparum genome. However, many of them remained annotated as putative proteins as their functionality has not been validated experimentally. So far, only five co-chaperones, PfHop, Pfp23, PfAha1, PfPP5 and PfFKBP35 have been characterized and shown to interact with PfHsp90. This review will summarize current knowledge on the co-chaperones in P. falciparum and discuss their regulatory roles on PfHsp90. As certain eukaryotic co-chaperones have also been implicated in altering the affinity of Hsp90 for its inhibitor, this review will also examine plasmodial co-chaperones' potential influence on approaches towards designing antimalarials targeting PfHsp90.